Touch, light, wounding: how anaesthetics affect plant sensing abilities - Pavlovič, Andrej (Plant cell reports, 2024)
Anaesthetics affect not only humans and animals but also plants. Plants exposed to certain anaesthetics lose their ability to respond adequately to various stimuli such as touch, injury or light. Available results indicate that anaesthetics modulate ion channel activities in plants, e.g. Ca2+ influx. The word anaesthesia means loss of sensation. Plants, as all living creatures, can also sense their environment and they are susceptible to anaesthesia. Although some anaesthetics are often known as drugs with well-defined target to their animal/human receptors, some other are promiscuous in their binding. Both have effects on plants. Application of general volatile anaesthetics (GVAs) inhibits plant responses to different stimuli but also induces strong cellular response. Of particular interest is the ability of GVAs inhibit long-distance electrical and Ca2+ signalling probably through inhibition of GLUTAMATE RECEPTOR-LIKE proteins (GLRs), the effect which is surprisingly very similar to inhibition of nerve impulse transmission in animals or human. However, GVAs act also as a stressor for plants and can induce their own Ca2+ signature, which strongly reprograms gene expression . Down-regulation of genes encoding enzymes of chlorophyll biosynthesis and pigment-protein complexes are responsible for inhibited de-etiolation and photomorphogenesis. Vesicle trafficking, germination, and circumnutation movement of climbing plants are also strongly inhibited. On the other hand, other cellular processes can be upregulated, for example, heat shock response and generation of reactive oxygen species (ROS). Upregulation of stress response by GVAs results in preconditioning/priming and can be helpful to withstand abiotic stresses in plants. Thus, anaesthetic drugs may become a useful tool for scientists studying plant responses to environmental stimuli.
Keywords: regulace genové exprese u rostlin; anestetika; Anesthetics; rostliny; Plants; světlo; Anaesthesia; Jasmonates; Carnivorous plant; Wounding; De-etiolation; Electrical signals; Touch; Light; hmat; Plant Physiological Phenomena; Gene Expression Regulation, Plant; fyziologie rostlin